New technique of producing removable complete denture using rapid tooling approach - Kassim, Noraniah (2012)
This thesis presents the development of a new approach for denture fabrication process by implementing the techniques used in the advanced manufacturing technology involving Computer Aided Design (CAD) and Rapid Tooling (RT) process. A 3D-ATOS scanning system was used to obtain the surface data of the edentulous model, occlusion rims of the patient and the teeth set received from the dental clinic. The scanned surface was refined using the Geomagic Studio 10 and then converted to IGES format for CAD application. A SolidWork version 2010 was used for designing reference lines, imaginary plane and setup curves to the 3D images of the scanned components. This was used as a reference for denture assembly in which, the design were followed to the occlusion and teeth arrangement principles and the data would then be stored in a CAD library for future design. Then maxilla anterior, maxilla posterior and mandible anterior teeth were assembled one by one while mandible posterior teeth were assembled by collision detection. Chewing detection was also conducted to check the contact region between upper and lower teeth by using interference detection technique. Then, new freeform surfaces were created for gingival and base plate. The complete dentures design were converted to STL format for production of master pattern using the Multi Jet Modelling (MJM) machine, one of the rapid prototyping (RP) technique. The pattern was used in the silicon rubber mould for vacuum casting process. Cold cure acrylic resin (VERTEX, Castavaria) was used as the denture material and casted in the silicone mould. Different degassing times were studied to reduce porosity dentures parts. Then, the final dentures were polished and tested on edentulous model to test the bite and adaptability. The finished denture was tested on patient edentulous to ensure the adaptability and comfortability. The result for the denture was found to be satisfactory and has good accuracy. While, from mechanical properties result was found the cold cure material which produced from the vacuum casting process has